A Dual‐Locked Activatable Phototheranostic Probe for Biomarker‐Regulated Photodynamic and Photothermal Cancer Therapy. Issue 26 (27th April 2022) - Wei, Xin; Zhang, Chi; He, Shasha; Huang, Jiaguo; Huang, Jingsheng; Liew, Si Si; Zeng, Ziling; Pu, Kanyi
Abstract: Activatable phototheranostics holds promise for precision cancer treatment owing to the "turn‐on" signals and therapeutic effects. However, most activatable phototheranostic probes only possess photodynamic therapy (PDT) or photothermal therapy (PTT), which suffer from poor therapeutic efficacy due to deficient cellular oxygen and complex tumor microenvironment. We herein report a dual‐locked activatable phototheranostic probe that activates near‐infrared fluorescence (NIRF) signals in tumor, triggers PDT in response to a tumor‐periphery biomarker, and switches from PDT to PTT upon detecting a tumor‐core‐hypoxia biomarker. This PDT‐PTT auto‐regulated probe exhibits complete tumor ablation under the photoirradiation of a single laser source by producing cytotoxic singlet oxygen at the tumor periphery and generating hyperthermia at tumor‐core where is too hypoxic for PDT. This dual‐locked probe represents a promising molecular design approach toward precise cancer phototheranostics. Abstract : A dual‐locked activatable phototheranostic probe is developed to turn on its near‐infrared fluorescence signal for real‐time imaging. Additionally, the probe can activate photodynamic therapy in response to γ‐glutamyl transferase in the tumor periphery and switch to photothermal therapy triggered by nitroreductase in the hypoxic tumor core.